2015
DOI: 10.1016/j.kjms.2015.05.001
|View full text |Cite
|
Sign up to set email alerts
|

Biliary stenting for unresectable cholangiocarcinoma: A population‐based study of long‐term outcomes and hospital costs in Taiwan

Abstract: Few studies have compared percutaneous biliary stenting (PBS) and endoscopic biliary stenting (EBS) in terms of long-term effects on cholangiocarcinoma (CC), and few have systematically evaluated outcome associations in Taiwan. This study aimed to compare long-term outcomes between two treatments for unresectable CC: PBS and EBS. After propensity score matching (PSM) to reduce the effect of selection bias, 1002 CC patients were included in this analysis: 501 in the PBS group and 501 in the EBS group. The Kapla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…The number of living patients with liver transplant has increased over the recent years given improvement in survival and emergence of gastrointestinal tumors has been reported recently. [ 10 , 11 ] We searched PubMed, and Chinese databases Wangfang and CNKI for literature on emergent neoplasms postliver transplant. Between January, 1993, and June, 2012, 47 papers were published on emergent neoplasms postliver transplant.…”
Section: Discussionmentioning
confidence: 99%
“…The number of living patients with liver transplant has increased over the recent years given improvement in survival and emergence of gastrointestinal tumors has been reported recently. [ 10 , 11 ] We searched PubMed, and Chinese databases Wangfang and CNKI for literature on emergent neoplasms postliver transplant. Between January, 1993, and June, 2012, 47 papers were published on emergent neoplasms postliver transplant.…”
Section: Discussionmentioning
confidence: 99%
“…A study by the Dutch Pancreatic Cancer Group demonstrated that although the use of palliative chemotherapy in patients with distal CCA improved over time, only 32.9% of patients received at least 1 line of palliative chemotherapy by 2016 ( 67 ). The limited use of systemic therapy in patients with ECC may in part be related to 1) worse nutritional and performance status due to patterns of metastasis (ie, high rates of multi-organ and peritoneal metastasis) ( 69-71 ) and 2) local tumor-related complications such as biliary obstruction leading to elevated liver function tests and recurrent cholangitis ( 2 , 5 , 35 , 70 , 72 , 73 ).…”
Section: Discussionmentioning
confidence: 99%